Animal agriculture and watershed management: Reconciling public and private good - Kaufmann, Ralph R. von; Mohamed-Saleem, M.A. (International Centre for Integrated Mountain Development, 2000)
The general stresses and problems that have to be addressed in establishing sustainable mountain agriculture include rapid population growth; farming on slopes and the associated erosion; remoteness and poor infrastructure resulting in poor access to markets and services; limited job opportunities; and political isolation and non participatory Development planning. This paper argues that something not only should but can and must be done to make research more relevant to individual mountain smallholders for the good of all. This will have to be carried out holistically at the watershed scale with livestock and a principle component. This Report borrows heavily from collaborative research in Ethiopia and Ethiopian Agricultural Research Organization, ICRISAT, ILRI and other colleagues that seek to determine the conflicting attributes of livestock in highland agriculture and thus develop technologies and policy options to ameliorate the negative attributes and accentuate the positive social and environmental effects.